Peran Guru dalam Menangani Gangguan Pendengaran pada Anak Usia Dini - Silvia Fahmi Ramadani; Hijriati; Suci Ramadhani; Uratun Aini; Yuni Mauliza (JURNAL BUNGA RAMPAI USIA EMAS, 2026)
Abstract: This study aims to identify the role of teachers in managing early childhood with hearing loss and the learning strategies implemented to support their communication and social interaction development. The study was conducted using descriptive qualitative methods. The subjects in this study consisted of early childhood education teachers and early childhood with hearing loss. Data collection was conducted through observation, interviews, and documentation. The research findings indicate that teachers function as facilitators, guides, motivators, and liaisons between schools and parents. The learning strategies implemented include the use of visual media, simple communication, body movements, interactive learning methods, and adjustments to the classroom environment. Challenges faced by teachers include minimal training, limited facilities, and a lack of understanding from parents. Therefore, collaboration between teachers, parents, and schools is needed to support optimal child development